Health Technology Assessment of Advanced Therapy Medicinal Products: Comparison Among 3 European Countries - Lucia Gozzo; Lucia Gozzo; Giovanni Luca Romano; Francesca Romano; Serena Brancati; Laura Longo; Daniela Cristina Vitale; Filippo Drago; Filippo Drago; Filippo Drago (Frontiers Media S.A., 2021)
Even for centrally approved products, each European country is responsible for the effective national market access. This step can result in inequalities in terms of access, due to different opinions about the therapeutic value assessed by health technology assessment (HTA) bodies. Advanced therapy medicinal products (ATMPs) represent a major issue with regard to the HTA in order to make them available at a national level. These products are based on genes, tissues, or cells, commonly developed as one-shot treatment for rare or ultrarare diseases and mandatorily authorized by the EMA with a central procedure. This study aims to provide a comparative analysis of HTA recommendations issued by European countries (France, Germany, and Italy) following EMA approval of ATMPs. We found a low rate of agreement on the therapeutic value (in particular the "added value" compared to the standard of care) of ATMPs. Despite the differences in terms of clinical assessment, the access has been usually guaranteed, even with different timing and limitations. In view of the importance of ATMPs as innovative therapies for unmet needs, it is crucial to understand and act on the causes of disagreement among the HTA. In addition, the adoption of the new EU regulation on HTA would be useful to reduce disparities of medicine's assessment among European countries.